Gene polymorphisms for patients with Class III malocclusion. A pilot study - Bahya, Aqeel M; Abid, Mushriq; Alsahafi, Elham (Journal of Baghdad College of Dentistry, 2024)
Background: The interactions of genetic and environmental factors may account for the variability in the expression of malocclusion. The study of malocclusion etiology is fundamental to understand the biology underlying craniofacial growth and dental relations. Understanding biology will improve progress toward effective treatment and prevention, thereby decreasing the burden of this condition. Aims: The present study was set out to investigate the association of the single nucleotide polymorphisms (SNPs) in different genes (rs2249492 in COLA1A, rs4434184 in SOX2, rs2162540 in FGFR2, rs11696257 in MAFB, and rs881301 in FGFR1) with Class III malocclusion. Materials and Methods: A total of 10 patients, comprising 5 with Skeletal Class I and 5 with Skeletal Class III malocclusion, were included in the present study. Salivary DNA samples were collected and analyzed using Sanger sequencing. Digital tracing was performed on lateral cephalometric radiographs by using AutoCAD software for digitization to assess the anterio-posterior and vertical relationship of the maxillary and mandibular arch. Results: Out of five genes polymorphisms only two genes polymorphisms (SOX2 and FGFR1) showed an association with Cl.III malocclusion. Conclusion: This study reveals that SOX2 and FGFR1 genetic polymorphisms may be responsible for Class III malocclusion. However, more study with a larger participant pool is required to confirm these findings.